Pengaruh Model Pembelajaran Role Playing Terhadap Hasil Belajar IPS Siswa Kelas IV UPTD SD Negeri 124391 Pematang Siantar - Rifka Sriwati Hutagaol; Jumaria Sirait; Emelda Thesalonika; Ipan Sihite (Departement of Mathematics Education, 2023)
This study aims to determine the effect of Role Playing learning model on social studies learning outcomes of fourth grade students of UPTD SD Negeri 124391 Pematang Siantar. This type of research is quantitative research. The sample in this study amounted to 30 students including 13 men and 17 women. The research instrument used in this study is a learning outcome test instrument. The data obtained by students who took the pretest and posttest as many as 30 students in the experimental class were the average pretest score of 56.06 and the average posttest score of 85.2 while the maximum pretest score was 76 and posttest 100, the minimum pretest score was 36 and the minimum posttest score was 60. The results of hypothesis testing on the N-gain test showed the results of the N-Gain score of 0.70 in the medium or moderately effective category. Based on the acquisition of pretest and posttest data, it can be concluded that the Role Playing learning model affects student learning outcomes and can improve student social studies learning outcomes.